Halogen bonding reduces intrinsic traps and enhances charge mobilities in halide perovskite solar cells. Issue 12 (6th March 2019) - Bi, Shiqing; Wang, Hui; Zhou, Jiyu; You, Shuai; Zhang, Yuan; Shi, Xinghua; Tang, Zhiyong; Zhou, Huiqiong
Abstract : Based an additive process, we demonstrate control over the crystallographic growth kinetics in polycrystalline perovskites with achieving high efficiency and stable perovskite solar cells. Abstract : Obtaining control over the crystallographic growth kinetics in polycrystalline perovskites has become a central topic toward achieving high efficiency and stable perovskite solar cells. Inspired by the chemistry of halogen bonding, we introduce an effective processing strategy using diiodoperfluoroalkyl and diiodoalkyl additives to modulate the crystallization, traps and resultant photophysical processes in methylammonium halide (CH3 NH3 PbI3 ) perovskite solar cells that can reach a power conversion efficiency (PCE) exceeding 20% associated with a negligible hysteresis with a compact TiO2 based planar structure. Aided by combinatorial analyses with X-ray photoelectron spectroscopy, dynamic light scattering and density functional theory calculation, we ascribe the achieved modulation of the crystallization in CH3 NH3 PbI3 to the formation of halogen bonding between the iodine in the additives and halide anions in perovskite precursor solutions. Benefitting from the modification with additives, the resultant solar cells exhibit a decrease in Shockley–Read–Hall recombination due to the suppressed charge trapping which explains the improvement of PCE. Our solar cells processed with additives also show retardation of degradation with a considerably enhanced environmental stability. This work offers a promising route through additive management to achieve high performance and stable perovskite solar cells.